Organizational Context and the Characteristics and Tenure of Hospital Administrators - Pfeffer, Jeffrey; Salancik, Gerald R. (Academy of Management Journal, 1977)
The professional background and tenure of hospital administrators were examined in relation to organizational size, competition for funding and staff, relations with the local business community, and sources of funds. The results are consistent with Thompson's (1967) argument that succession to leadership positions is related to the ability to cope with organizational uncertainties.